The Effect Of Coenzim Q10 On The Number Of Lymfocite Cells In Male Wistar Rats With Periodontitis - Tara Yurian Nadhifa; Aprilia Yuanita Anwaristi; Nur Ariska Nugrahani; Dwi Kurniawati (Jurnal EduHealth, 2023)
Periodontal disease is a dental and oral health problem in adult society. One of the periodontal diseases is periodontitis which is an inflammation of the periodontal tissue caused by accumulation of dental plaque which can lead to impaired masticatory function, tooth loss, alveolar bone damage, periodontal ligament damage, pocket formation, and gingival recession. Coenzyme Q10 acts as an antioxidant, the reduced form is ready to give electrons to deactivate ROS or block free radicals which can prevent oxidative stress thereby protecting lymphocyte cells and reducing the immune response which can lead to a reduction in inflammation in the periodontal tissues. The purpose of this study was to determine the effect of coenzyme Q10 on the number of lymphocyte cells in the gingiva of male wistar rats with periodontitis. The research method used is true experimental laboratory quantitative research with a research design that is a posttest only control group design with observation or observing the control group and the treatment group. The number of samples used was 24 rats. Observation of lymphocyte cells was carried out using a light microscope with a magnification of 200x and a magnification of 400x and then counted manually by the observer. The results showed that the significance value obtained in the One-Way ANOVA test was 0.000 (<0.05). Then, based on the results of the Post Hoc Least Significant Difference (LSD) test, it was found that the biggest difference in effect was in the K(-)5 group and the P5 group, where the difference was 59.00 with a significance value of 0.000 (<0.05). It can be concluded that there is an effect of coenzyme Q10 administration on the number of lymphocyte cells in the gingiva of male Wistar rats with periodontitis.